CERDAS GIZI DI USIA ANAK SEKOLAH: PROGRAM EDUKASI DAN PENDIDIKAN KESEHATAN STATUS GIZI SEBAGAI UPAYA PENINGKATAN KESEHATAN SISWA - Muchti Yuda Pratama; Purwaningsih Purwaningsih; Nisrina Nisrina; Evamona Evamona; Roudatul Hasana (MAJU : Indonesian Journal of Community Empowerment, 2026)
School-age children represent an important phase in the human life cycle, characterized by rapid growth and development, both physically, psychologically, and socially. During this phase, nutritional needs increase significantly to support optimal growth. However, various nutritional problems are still frequently found among elementary school children, such as undernutrition, overnutrition (overweight and obesity), and micronutrient deficiencies such as anemia. In Indonesia, nutritional problems among elementary school-age children remain an important public health issue. Unbalanced dietary patterns, the habit of skipping breakfast, consumption of fast food, and low nutritional literacy are the main factors influencing the nutritional status of elementary school children. The purpose of this activity, as an effort to improve the health of elementary school-age children, is expected to increase the knowledge of students at SD Negeri 060801 Medan. The activity was carried out on June 29, 2026, from 09.00 to 12.00 WIB (Western Indonesia Time), at SD Negeri 060801 Medan. The methods used included lectures, discussions, and questionnaire administration. Based on the pretest questionnaire results, the participants' level of knowledge was categorized as good for 11 people (36.6%), sufficient for 12 people (40.0%), and poor for 7 people (23.3%). Meanwhile, based on the posttest questionnaire results, the participants' level of knowledge was categorized as good for 20 people (63.3%), sufficient for 7 people (23.3%), and poor for 3 people (10%).